Implementation of 21st Century Learning through the Development of ICT-Assisted Learning Media in Elementary School - IZZAN MUHAMMAD FURKAN; Fitria Yanti (Universe, 2023)
This research is motivated by the lack of available learning media for integrated thematic learning in Theme 6: Heat and Its Transfer, based on ICT (Information and Communication Technology) in schools. One of the ICT-based media is Articulate Storyline 3, designed to be as attractive as possible by incorporating audio, images, videos, games, and quizzes, aiming to motivate and actively engage students in learning. This research is a development research (R&D) using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The results of this research obtained an average validation score of 94.9% with a valid category. The teacher's questionnaire response obtained a score of 93.75% with a highly practical category, while the student's questionnaire response at SDN 07 Pasar Salido obtained a score of 97.92% with a highly practical category. The student's questionnaire response on the media deployment at SDN 22 Kampung Luar Salido obtained a score of 94.79% with a highly practical category. The effectiveness of the learning media at SDN 22 Kampung Luar Salido, based on the percentage of improvement in student learning outcomes, showed an average increase. In the 4th lesson at SDN 22 Kampung Luar Salido, it was 95% with a highly effective category, while in the 5th lesson at SDN 22 Kampung Luar Salido, it was 90% with a highly effective category. Thus, it can be concluded that Articulate Storyline 3 media is deemed suitable for use in teaching and learning.